Konka Board: a cement-pumice-tow sheathing board - Isaacs, Nigel (Architectural History Aotearoa, 2021)
Konka board was a New Zealand invention which combined cement, pumice and flax fibre ("tow") into a fibre-cement board, replacing the imported asbestos-cement sheet. Sold soon after manufacture, Konka, it could be nailed or screwed, and over time it hardened. A waterproof plain or stucco plaster finish provided a resilient, borer proof, fireproof, low maintenance house. Three patents created the Konka system – 34,845 for the fibre-reinforced board, 37,354 for the stud and support system into which a concrete grout was poured to lock the panels in place, and finally 52,50 for metal strips to ensure a smooth final plaster surface. A waterproofing additive in the plaster provided the final part of the system. The company quickly setup a national series of agents, with manufacturing ultimately occurring in Wanganui, Gisborne, Christchurch and Timaru. Patent 34,845 was challenged in 1927, with the Privy Council finding in 1930 that it was invalid, opening the way for similar products to be made. The development in the 1930s of NZSS 95 Model Building By-law allowed Konka to be used nationally, without further evidence as to its performance. However, competitor other products were also included e.g. Excell, Rotorua, Thermax, Duro, Wangan, Walasco and the asbestos based Fibrolite. Konka survived until the 1960s, when flax production was in decline, the high labour costs and manufacturing time meant it was no longer competitive. Even so, in a twist of fate it was a Konka style approach which led to cellulose fibre replacing asbestos in fibre-cement sheeting. In the twenty-first century, Konka could even be considered a desirable product – a natural fibre reinforced, composite sheet.